Protocolos de leitura em obras de Maria José Dupré na Série Vaga-Lume: livros, leitura e literatura para jovens leitores no século XX - Silva, Josineia Sousa da (2017)
This bibliographical-documentary and historical-cultural matrix study is dedicated to understand protocols for reading literary texts in correlation with representations of readers evidenced on literary reading objects published for young readers in the last decades of the twentieth century, from the Study of different editions of the works Éramos Seis and A ilha Perdida, by Maria José Dupré, in the context of the VagaLume editorial series. The series in question was important in the Brazilian scenario in the formation of different generations of readers and in the viability of numerous teaching-learning processes of literary reading, participating, in a substantial way, in the delineation of the idea of young reader and of juvenile literature, in the last decades of the twentieth century, through its high impression and extensive circulation. Given the discussions about the different types, regimes and modalities of reading in correlation with diverse cultural objects and the discussions about the unequal presence of the book and of literature in specific social contexts, the investigation in question explores protocols of readings and representations of readers enrolled in literary works in the time, mode and space in which they were written, published and circulated more evidently. It covers the production of the data the literary narrative as well as the materiality of the object book and of the printed matter related to it. For this, we adopted a theoretical reference pertinent to Cultural History and, in particular, to the thought of Roger Chartier and other authors of compatible epistemological orientation. In this sense, the results point towards the importance of the materiality of texts in literature and reading studies, more specifically, in the works now discussed, inscribed in the last decades of the twentieth century in Brazil.